2019
DOI: 10.3390/cells8020086
|View full text |Cite
|
Sign up to set email alerts
|

The Catalase Gene Family in Cotton: Genome-Wide Characterization and Bioinformatics Analysis

Abstract: Catalases (CATs), which were coded by the catalase gene family, were a type notably distinguished ROS-metabolizing proteins implicated to perform various physiological functions in plant growth, development and stress responses. However, no systematical study has been performed in cotton. In the present study, we identified 7 and 7 CAT genes in the genome of Gossypium hirsutum L. Additionally, G. barbadense L., respectively. The results of the phylogenetic and synteny analysis showed that the CAT genes were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 95 publications
(141 reference statements)
5
66
0
Order By: Relevance
“…This result is possibly because only one or two miRNAs regulated the isoforms of the GhCIPKs or only part of the isoforms transcribed from GhCIPK genes were detected from our mRNA-seq data. Similar phenomena could also be detected in the cotton CAT gene family in Figure S6 [39].…”
Section: Predictions Of Putative Molecular Regulatory Mechanisms Of Gsupporting
confidence: 80%
See 3 more Smart Citations
“…This result is possibly because only one or two miRNAs regulated the isoforms of the GhCIPKs or only part of the isoforms transcribed from GhCIPK genes were detected from our mRNA-seq data. Similar phenomena could also be detected in the cotton CAT gene family in Figure S6 [39].…”
Section: Predictions Of Putative Molecular Regulatory Mechanisms Of Gsupporting
confidence: 80%
“…A total of 80 and 78 CIPK genes were identified in G. hirsutum and G. barbadense, respectively (Tables S2 and S3). The number of CIPK genes in each of the G. hirsutum and G. barbadense genome was greater than that in Arabidopsis (26) and rice (34), and was basically equal to the total sum of G. raimondii (41) and G. arboretum (39), suggesting that the CIPK gene family expands during evolution. G. raimondii and G. arboretum underwent a Gossypium-specific whole-genome duplication (WGD) [27,30,31], and the CIPK gene family of G. raimondii and G. arboretum may expand by an ancient WGD event.…”
Section: Phylogenetic Analysis and Evolution Of Cipk Genes In Gossypiummentioning
confidence: 85%
See 2 more Smart Citations
“…In the present study, we identified 151 Pkinase genes in three cotton species, G. raimondii, G. arboreum and G. hirsutum, which were found to have 41, 35 and 75 genes, respectively. The number identified in upland cotton (G. hirsutum) was relatively higher (more than double) than in G. arboreum and G. raimondii, which indicates that whole genome duplication (WGD) or polyploidy events played a major role in Pkinase gene family expansion [67]. Allotetraploid cotton possibly emerged from the polyploidization of the A and D genomes, suggesting that the expansion of Pkinase family genes from diploid to allotetraploid cotton is mainly a consequence of gene duplication and the conservation of the Pkinase genes during the polyploidization process.…”
Section: Discussionmentioning
confidence: 99%